2007
DOI: 10.1007/s10295-007-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cellulose-binding domain on the catalytic activity of a β-glucosidase from Saccharomycopsis fibuligera

Abstract: Enzyme engineering was performed to link the beta-glucosidase enzyme (BGL1) from Saccharomycopsis fibuligera to the cellulose-binding domain (CBD2) of Trichoderma reesei cellobiohydrolase (CBHII) to investigate the effect of a fungal CBD on the enzymatic characteristics of this non-cellulolytic yeast enzyme. Recombinant enzymes were constructed with single and double copies of CBD2 fused at the N-terminus of BGL1 to mimic the two-domain organization displayed by cellulolytic enzymes in nature. The engineered S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Cellulases (exoglucanases and endoglucanases) possess cellulose binding domains that are crucial for these enzymes to interact with their substrate cellulose (45). To improve the activity of single cellulolytic enzymes expressed and secreted by S. cerevisiae, domain engineering of cellulose binding domains has been a frequent target in the recent past (109,130,229).…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…Cellulases (exoglucanases and endoglucanases) possess cellulose binding domains that are crucial for these enzymes to interact with their substrate cellulose (45). To improve the activity of single cellulolytic enzymes expressed and secreted by S. cerevisiae, domain engineering of cellulose binding domains has been a frequent target in the recent past (109,130,229).…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…Further, Sarath reported the effect of a fungal CBD on the enzymatic characteristics of the β-glucosidase from Saccharomycopsis fibuligera . The fusion enzyme displayed a 2–4 fold increasing in their hydrolytic activity toward cellulosic substrates [11]. In the present study, we successfully over-expressed the β-glucosidase (BGL) gene from T. thermosaccharolyticum DSM 571 in E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…Ni-NTA affinity purification of the soluble fraction resulted in a >90% purified enzyme as detected by SDS-PAGE and β-glucosidase activity assay. As fusion of a binding module has been shown to alter the activity and the thermal stability of the catalytic domain (28,29), the kinetic parameters (K m and k cat ), thermal stability and the optimal pH and temperature profiles of BglA-CohII were determined and compared to those of the wild-type enzyme (WT BglA). The thermal stability assay revealed that BglA-CohII retains 80% of its initial activity after 3 h at 60°C as compared to 91% retention of the activity shown by WT BglA thus indicating a decrease of 13%.…”
Section: Resultsmentioning
confidence: 99%